REAKSI SIGNAL FAKTOR MAKROEKONOMI, FUNDAMENTAL, DAN RESIKO SISTEMIS (BETA SAHAM) TERHADAP RETURN SAHAM SYARIAH YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Purboyo Purboyo; Rizka Zulfikar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This study aims to determine the effect of macroeconomic factors, corporate fundamentals and systemic risk on the return of Islamic stocks listed on the Indonesian stock exchanges incorporated in Jakarta Islamic Index (JII) stocks during the period 2013 to 2016, the sampling of data using purposive sampling method, there are 11 syariah-compliant companies which for four years or eight consecutive times entered into JII index during the observation period between 2013 and 2016 sampled, while the variables studied consist of GDP (Gross Domestic Product), inflation, DER (Debt to Equity Ratio), ROA (Return On Assets), BETA (systemic risk) and stock return. The test method using multiple regression analysis with SPSS test, the result of statistical test with F test (F-test) got the result that all independent variables (GDP, inflation, DER, ROA, BETA) simultaneously have significant effect to stock return with significance level 0,002 , the result of statistical test with t test (t-test) there are two variables that is inflation with significance level 0,017 and DER with significance level 0,030 have significant effect to return of syariah stock, while other variable that is GDP, ROA and BETA have no significant effect to stock return sharia. Keywords: Sharia stock, GDP, Inflation, Corporate fundamentals, systemic risk, Stock return